[1]Benzothieno[3, 2-b][1]benzothiophene-based dyes: effect of the ancillary moiety on mechanochromism and aggregation-induced emission. Issue 24 (14th June 2022) - Shivaji, Babar Suraj; Boddula, Rajamouli; Singh, Surya Prakash
Abstract : Strategic design of [1]benzothieno[3, 2- b ][1]benzothiophene (BTBT) derivatives (donor–π–acceptor–π–donor) towards AIE, MFC and halo-MFC properties. Abstract : It is an established fact that [1]benzothieno[3, 2- b ][1]benzothiophene (BTBT) is a champion molecule for high-mobility OFET devices. Recently, it has also been utilized in dye-sensitized solar cells (DSSCs) and organic photovoltaics (OPVs) as an alternative to fullerene (non-fullerene acceptor). Considering the advantageous features of BTBT, we herein report its aggregation-induced emission (AIE) and mechanofluorochromic (MFC) behaviour for the first time. We have designed and synthesized two new BTBT derivatives: [1]benzothieno[3, 2- b ][1]benzothiophene-tetraphenylethylene (BTBT-TPE ) and [1]benzothieno[3, 2- b ][1]benzothiophene-phenyl- N, N -dimethylamine (BTBT-NMe ). The donor–π–acceptor–π–donor-integrated BTBT-TPE showed AIE whereas BTBT-NMe showed aggregation-caused quenching (ACQ), as evident by their quantum yield and lifetime results. BTBT-NMe was found to possess great interaction, resulting in the halochromic (protonation) effect. The theoretical calculation of the electronic distribution and energy investigation were consistent with the experimental outcomes. The electron contribution of the HOMO is high for BTBT-NMe at the donor, which can be attributed to the weaker donating nature of TPE compared to that of the NMe group. Overall, the results indicate the potential of the mechanical stimuli and aggregation response of the studied compounds for further investigation.